Pengaruh Moral Disengagement Dan Self-Esteem Terhadap Perilaku Bullying Siswa Di Pondok Pesantren Dengan School Climate Sebagai Variabel Moderator - Arwani, Muhammad; Layyinah, Layyinah (Peneliti.net, 2025)
Bullying behavior in schools, including pesantren, has become a global phenomenon that has an impact on the psychological well-being of students. The purpose of this study is to determine the effect of moral detachment, self-esteem, and school climate on the bullying behavior of students at Sipurs Purwakarta Islamic Boarding School. This study also analyzes whether school climate can moderate the relationship between moral indifference and self-esteem in bullying behavior. The approach used is a quantitative approach where data is collected through a survey of Madrasah Aliya (MA) Pondok Pesantren Sipurs students who are involved in bullying behavior in the 2024-2025 school year. The results of this study are expected to provide a deeper understanding of the psychological factors that influence bullying behavior in the pesantren environment and the role of the school environment in reducing the intensity of bullying. The results of this study provide theoretical contributions to the development of educational psychology and practical benefits in the development of policies and interventions that can create a safer school environment and support students' social and psychological development. This study also aims to provide insights to educators and schools about the importance of creating a positive school environment to prevent bullying.